DRY MATTER PRODUCTION AND NUTRIENT CONTENT OF MAMEY SAPOTE GROWN ON AN ACID ULTISOL. (13th February 2018) - GOENAGA, RICARDO
SUMMARY: Little is known about the adaptability of mamey sapote ( Pouteria sapota ) to acidic soils high in aluminum (Al). A 2 year field study was conducted to determine the effects of various levels of soil Al on dry matter production, stem diameter and nutrient concentration in tissues of four cultivars of mamey sapote. Soil Al treatments were statistically different for all variables measured in the study. Cultivars and the year × cultivar interaction were not significant; therefore, results were averaged over cultivars and years. Increasing soil Al concentration from 3.5 to 7.8 cmol kg −1 resulted in an increase in total dry weight, but higher soil Al concentrations resulted in dry weight and stem diameter reductions. Increments in soil Al resulted in a significant reduction in the concentration of leaf, stem and root calcium. The Al concentration in leaf and stem tissues was not significantly affected with increments in soil Al, but there was a significant decline in the concentration of Al in root tissue suggesting that mamey sapote may exclude Al from roots.